Intimate Partner Violence, Clinical Indications, and Other Family Risk Factors Associated With Pediatric Abusive Head Trauma. Issue 9 (May 2022) - Sayrs, Lois W.; Ortiz, J. Bryce; Notrica, David M.; Kirsch, Lisa; Kelly, Cara; Stottlemyre, Rachael; Cohen, Aaron; Misra, Shivani; Green, Tabitha R.; Adelson, P. David; Lifshitz, Jonathan; Rowe, Rachel K.
Over half of fatal pediatric traumatic brain injuries are estimated to be the result of physical abuse, i.e., abusive head trauma (AHT). Although intimate partner violence (IPV) is a well-established risk for child maltreatment, little is known about IPV as an associated risk factor specifically for AHT. We performed a single-institution, retrospective review of all patients (0–17 years) diagnosed at a Level 1 pediatric trauma center with head trauma who had been referred to an in-hospital child protection team for suspicion of AHT between 2010 and 2016. Data on patient demographics, hospitalization, injury, family characteristics, sociobehavioral characteristics, physical examination, laboratory findings, imaging, discharge, and forensic determination of AHT were extracted from the institution's forensic registry. Descriptive statistics (mean, median), chi-square and Mann–Whitney U tests were used to compare patients with fatal head injuries to patients with nonfatal head injuries by clinical characteristics, family characteristics, and forensic determination. Multiple logistic regression was used to estimate adjusted odds ratios for the presence of IPV as an associated risk of AHT while controlling for other clinical and family factors. Of 804 patients with suspicion for AHT in the forensic registry, there were 240 patients with a forensic determination of AHT; 42 injuries were fatal. There were 101 families with a reported history of IPV; 64.4% of patients in families with reported IPV were <12 months of age. IPV was associated with a twofold increase in the risk of AHT (Exp( β ) = 2.3 [ p = .02]). This study confirmed IPV was an associated risk factor for AHT in a single institution cohort of pediatric patients with both fatal and nonfatal injuries. Identifying IPV along with other family factors may improve detection and surveillance of AHT in medical settings and help reduce injury, disability, and death.